Is Trust in Banks in Slovenia Put to the Test? - Taškar Beloglavec, Sabina; Šebjan, Urban (Naše gospodarstvo/Our economy, 2015)
The question of the banking system’s stability in connection to trust since the 2008 crisis has been the subject of many debates seeking to find permanent solutions to banking system problems, as the current situation affects bank customers’ behavior. This article examined trust in banks during the financial crisis and offers, via demographic variables, explanations as tow whether or not customers tend to withdraw their deposits during a crisis. The results contribute to banks’ decision-making regarding deposits management and understanding customers’ behavior, especially during a crisis. The results show a negative relationship between trust and deposit withdrawal intention, where gender and education level play an important role.